2013
DOI: 10.1016/j.neuropsychologia.2013.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Differential roles for medial prefrontal and medial temporal cortices in schema-dependent encoding: From congruent to incongruent

Abstract: Information that is congruent with prior knowledge is generally remembered better than incongruent information. This effect of congruency on memory has been attributed to a facilitatory influence of activated schemas on memory encoding and consolidation processes, and hypothesised to reflect a shift between processing in medial temporal lobes (MTL) towards processing in medial prefrontal cortex (mPFC). To investigate this shift, we used functional magnetic resonance imaging (fMRI) to compare brain activity dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

31
250
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 258 publications
(306 citation statements)
references
References 27 publications
31
250
1
3
Order By: Relevance
“…On the other hand, consolidation-related theta power in frontal areas, and the fact that the results point consistently towards a specific role for REM sleep and not SWS, may appear strange at first glance, and at odds with the standard model of consolidation. However, a recent series of studies by van Kesteren et al (van Kesteren, Rijpkema, et al, 2010;van Kesteren et al, 2013; looking at the neural mechanisms underpinning the consolidation of schema-conformant items, suggest a possible modification of the standard model to take into account how well new memories fit with existing schemata, with tightly linked memories following a more rapid consolidation path.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, consolidation-related theta power in frontal areas, and the fact that the results point consistently towards a specific role for REM sleep and not SWS, may appear strange at first glance, and at odds with the standard model of consolidation. However, a recent series of studies by van Kesteren et al (van Kesteren, Rijpkema, et al, 2010;van Kesteren et al, 2013; looking at the neural mechanisms underpinning the consolidation of schema-conformant items, suggest a possible modification of the standard model to take into account how well new memories fit with existing schemata, with tightly linked memories following a more rapid consolidation path.…”
Section: Discussionmentioning
confidence: 99%
“…Once again, they also observed an important role for the mPFC, in this case an enhanced coupling between mPFC and somatosensory cortex (implicated in memory for the fabric). The final study by van Kesteren et al (van Kesteren et al, 2013) used a similar but slightly simplified congruency paradigm, in this case directly looking at object-scene pairings which were congruent or not, with functional neuroimaging of retrieval. This study once again revealed an enhanced role for the mPFC for schema-dependent items, and also found a decreased role for the hippocampus for these items.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the vmPFC is anatomically (Ongür and Price, 2000;Saleem et al, 2008) and functionally (Ranganath et al, 2005;AndrewsHanna et al, 2010) connected with MTL regions supporting memory. Reflecting that connectivity, vmPFC (or a homologous region) is activated when schematic or contextual memory is exercised as shown in animal models (Euston and McNaughton, 2006;Tse et al, 2007Tse et al, , 2011 and neuroimaging studies (Kumaran et al, 2009;van Kesteren et al, 2010;Bonnici et al, 2012;Zeithamova et al, 2012a). In this context, it is notable that severe declarative memory impairments after vmPFC damage are uncommon (Janowsky et al, 1989;Stuss et al, 1994), although damage to vmPFC (sometimes extending to surrounding regions) may increase confabulation and false recognition (DelbecqDerouesné et al, 1990;Umeda and Kato, 2000;Umeda et al, 2001;Gilboa et al, 2006).…”
Section: Introductionmentioning
confidence: 96%
“…A recent proposal (van Kesteren et al, 2012) suggested that medial prefrontal cortex (PFC) plays a critical role for new memories that overlap with existing knowledge, effectively weighting the influence of schematic memory. For example, increasing the weight of schematically related memories when recalling words fitting a "winter" schema would increase the probability of recalling the nonstudied word "snow" (as in the DRM paradigm).…”
Section: Introductionmentioning
confidence: 99%